2016
DOI: 10.1103/physreve.94.032604
|View full text |Cite
|
Sign up to set email alerts
|

Plastic response and correlations in athermally sheared amorphous solids

Abstract: The onset of irreversible deformation in low-temperature amorphous solids is due to the accumulation of elementary events, consisting of spacially and temporally localized atomic rearrangements involving only a few tens of atoms. Recently, numerical and experimental work addressed the issue of spatio-temporal correlations between these plastic events. Here, we provide further insight into these correlations by investigating, via molecular dynamics (MD) simulations, the plastic response of a two-dimensional amo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Localized defects of different nature have been discussed in the context of glasses, see e.g. [1][2][3][4][5][6][7][43][44][45][46], and our findings could be related to at least some of those theoretical proposals. Future work should clarify these connections, both by additional numerical simulations and analytical calculations.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Localized defects of different nature have been discussed in the context of glasses, see e.g. [1][2][3][4][5][6][7][43][44][45][46], and our findings could be related to at least some of those theoretical proposals. Future work should clarify these connections, both by additional numerical simulations and analytical calculations.…”
Section: Discussionmentioning
confidence: 74%
“…Within this framework, defects such as vacancies and dislocations can be treated as small perturbations. This description breaks down for amorphous solids such as glasses, foams, emulsions, plastics, colloids, granular materials, bacterial colonies, and tissues [1][2][3][4][5][6][7]. In these systems, the identification of "defects" becomes challenging because the solid ground state is strongly disordered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our next projects will follow mainly two directions: firstly, we want to run improved simulations, aimed to a finer characterization of the avalanches in finite dimensional systems. Secondly, in this article the maximum shear-strain was kept small in order to remain in the linear regime, but there is also much interest on the stationary elastoplastic regime that follows the yielding transition; we plan to study the distribution of avalanches in this setting, in order to be able to compare our results with all the works that have been published in the field, for example [36,37,38,39,40,41,42,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that in deeply supercooled liquids (parent liquids) relaxation of the Green-Kubo stress correlation function at large times corresponds to the relaxation of the Green-Kubo stress correlation function calculated on the inherent structures (i.e., on the structures obtained through "an instant quench" from the parent liquid structures) [4][5][6]19]. Another direction in the considerations of the stress relaxation concerns the angular dependence of changes in the stress fields generated by local structural transformations [15,17,18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%